2012
DOI: 10.1007/s12275-012-2336-6
|View full text |Cite
|
Sign up to set email alerts
|

Biological and genetic properties of SA14-14-2, a live-attenuated Japanese encephalitis vaccine that is currently available for humans

Abstract: Japanese encephalitis virus (JEV), a mosquito-borne flavivirus, is a major cause of acute encephalitis, a disease of significance for global public health. In the absence of antiviral therapy to treat JEV infection, vaccination is the most effective method of preventing the disease. In JE-endemic areas, the most widely used vaccine to date is SA(14)-14-2, a live-attenuated virus derived from its virulent parent SA(14). In this study, we describe the biological properties of SA(14)-14-2, both in vitro and in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 90 publications
4
28
0
Order By: Relevance
“…Recombinant JEVmut14-14-2 also produced small plaques but had a moderately lower mean peak titer of 6.4 log 10 PFU/mL (Table 3), which is consistent with the titer reported for JEV SA14-14-2 in baby hamster kidney cells. 48 Recombinant JEVmut14-14-2-C292T, with reversion mutation C-S66L, replicated to a significantly higher mean peak titer of 7.1 log 10 PFU/mL, similar to most JEV SA14-14-2 variants (Table 3). The JEV SA14-14-2 variant 3 IFN had a single unique reversion mutation, NS2A-V40A, relative to JEV SA14-14-2 variant D ( Table 1) that significantly increased mean peak virus titer ( Table 3).…”
Section: Resultsmentioning
confidence: 75%
See 4 more Smart Citations
“…Recombinant JEVmut14-14-2 also produced small plaques but had a moderately lower mean peak titer of 6.4 log 10 PFU/mL (Table 3), which is consistent with the titer reported for JEV SA14-14-2 in baby hamster kidney cells. 48 Recombinant JEVmut14-14-2-C292T, with reversion mutation C-S66L, replicated to a significantly higher mean peak titer of 7.1 log 10 PFU/mL, similar to most JEV SA14-14-2 variants (Table 3). The JEV SA14-14-2 variant 3 IFN had a single unique reversion mutation, NS2A-V40A, relative to JEV SA14-14-2 variant D ( Table 1) that significantly increased mean peak virus titer ( Table 3).…”
Section: Resultsmentioning
confidence: 75%
“…JN604986) of a commercial batch of JEV SA14-14-2 vaccine (Table 1). 48 Careful examination of the sequence chromatograms revealed that there were also minor secondary peaks at several positions throughout the genome indicating there was a mixture of nucleotides and predicted amino acid substitutions (Table 1). Biological cloning of this virus stock in Vero cells resulted in the isolation of six genetically distinct, Vero cell-adapted variants (A, B, C, D, G, and H).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations